Polymorphic variants near 1p22 and 20q11.2 loci and the risk of non-syndromic cleft lip and palate in South Indian population. Issue 12 (December 2015) - Babu Gurramkonda, Venkatesh; Hussain Syed, Altaf; Murthy, Jyotsna; Chaubey, Gyaneshwer; Bhaskar Lakkakula, V.K.S.
Abstract: Background: Recent genome-wide association studies (GWAS) have reported multiple genetic risk loci for non-syndromic orofacial clefts (NSOFCs) in many populations. However, the contribution of these loci to NSOFC in India, which comprises one-fifth of the global population, is completely lacking. Our aim was to replicate the association of the SNPs located on 1p22 chromosomal loci (rs540026, rs481931) and 20q11.2 (rs13041247, rs11696257) in the aetiology of NSOFCs, in South Indian populations. Methods: The SNPs were genotyped by using KBiosciences KASPar SNP genotyping chemistry in 173 cases and 176 controls for NSOFCs in South India. To estimate the association between these SNPs and NSOFCs, chi-square test was adopted. Odds ratios (OR) with 95% confidence intervals (CI) were also calculated in order to assess the risk. Results: Single nucleotide polymorphisms located at chromosomal region 1p22 are not found to be associated with cleft lip with or without non-syndromic cleft palate (NSCL/P) and non-syndromic cleft palate only (NSCPO) at either the genotype or allele levels. Further, there is no LD observed between these variants. The polymorphic variants near 20q11.2 (rs13041247, rs11696257) are in complete linkage disequilibrium (LD) and are significantly associated with only NSCL/P in genotypic ( p = 0.013) and allelic models ( p = 0.029). In the genotypic model significance persisted even after Bonferroni correction ( p < 0.016). Conclusion: These results suggest that 20q11.2 SNPs could play a contributory role in the pathophysiology and risk of NSCL/P, while the variations in 1p22 do not underlie the pathophysiology of NSOFCs in South Indian populations.